1999
DOI: 10.1017/s030500099900392x
|View full text |Cite
|
Sign up to set email alerts
|

Some differences between English plural noun inflections and third singular verb inflections in the input: the contributions of frequency, sentence position, and duration

Abstract: Grammatical inflections such as the English plural noun -s and third person singular verb -s are acquired at different points in time by young children. This finding is typically attributed to factors such as relative semantic salience or the distinction between lexical and functional categories. In this study input frequency, sentence position, and duration were examined as possible contributing factors. In both conversations with and stories aimed at young children, noun plural inflections were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 0 publications
2
76
1
Order By: Relevance
“…In addition to coda complexity, we examined whether the position of the third person singular morpheme within the utterance influenced children's production of third person singular -s. In subject-verb-object languages such as English, children hear third person singular verbs more often in utterance-medial position than in utterance-final position (Hsieh et al, 1999). Similarly, we found that 72% of the children's attempted third person singular verbs in this study occurred in utterance-medial position.…”
Section: Alexsupporting
confidence: 75%
See 3 more Smart Citations
“…In addition to coda complexity, we examined whether the position of the third person singular morpheme within the utterance influenced children's production of third person singular -s. In subject-verb-object languages such as English, children hear third person singular verbs more often in utterance-medial position than in utterance-final position (Hsieh et al, 1999). Similarly, we found that 72% of the children's attempted third person singular verbs in this study occurred in utterance-medial position.…”
Section: Alexsupporting
confidence: 75%
“…Leonard and colleagues (e.g., Leonard & Bortolini, 1998) have raised the possibility that inflectional morphemes might be especially vulnerable and are likely to be omitted because they are composed of phonetically short elements that might be difficult to perceive. This problem is exacerbated in the case of English verbs, as these tend to occur utterance-medially in parental speech, whereas plural nouns tend to occur utterance-finally (Hsieh, Leonard, & Swanson, 1999). Hsieh et al (1999) report that, as a consequence of this difference in distribution, third person singular -s is much shorter in duration compared with plural -s, perhaps reducing the perceptional salience of the third person singular morpheme.…”
Section: A Phonological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Rumelhart and McClelland 1986), take statistical properties of the input to be the primary determinant of development, and some acquisition studies have shown that the relative frequency of particular pieces of morphology (e.g. Hseieh et al (1999)) and of particular lexical items such as verbs (Naigles and Hoff-Ginsberg 1998) correlate with their order of acquisition in the child's language. It has also been proposed that the acquisition of particular syntactic constructions, for example wh questions, is affected by the relative frequency of specific wh + verb combinations in the input (Rowland et al 2003).…”
Section: Frequency Effects In the Acquisition Of The Malagasy Voicesmentioning
confidence: 99%